2012
DOI: 10.1007/s00421-012-2345-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ischemic preconditioning on aerobic and anaerobic variables associated with submaximal cycling performance

Abstract: Acute limb ischemia induced by pressure cuffs before activity (ischemic preconditioning; IPC) has been reported to improve exercise performance at maximal efforts. The purpose of this investigation was to determine the effects of IPC during a submaximal performance test in competitive amateur level cyclists. Twelve healthy, male cyclists participated in two performance tests in which they cycled at successive relative intensities of 30, 50, and 70% of their maximal power output for 5 min each. The test culmina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
4
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 18 publications
6
65
4
4
Order By: Relevance
“…Similarly, IPC improved peak power output during maximal incremental leg cycling 10,13) . By contrast, other studies reported no effect of IPC on exhaustion time during maximal incremental leg cycling 14) , constant load leg cycling at an intensity of 130% of the peak power output 10) , the time needed to cycle 100 kJ of total work 15) . Additionally, IPC did not show any beneficial effects on increasing the maximal power output during maximal incremental leg cycling 16) .…”
Section: Sprint (Cycle) Performancementioning
confidence: 60%
See 4 more Smart Citations
“…Similarly, IPC improved peak power output during maximal incremental leg cycling 10,13) . By contrast, other studies reported no effect of IPC on exhaustion time during maximal incremental leg cycling 14) , constant load leg cycling at an intensity of 130% of the peak power output 10) , the time needed to cycle 100 kJ of total work 15) . Additionally, IPC did not show any beneficial effects on increasing the maximal power output during maximal incremental leg cycling 16) .…”
Section: Sprint (Cycle) Performancementioning
confidence: 60%
“…Likewise, the heart rate peak (HRpeak) was not increased with IPC during maximal incremental leg cycling 13) , during constant load leg cycling until exhaustion 11,12) , maximal HR during a 5 km running time trial 21) , and 100 m swimming 19) . Additionally, maximum pulmonary ventilation (V ・ Emax) during maximal incremental leg cycling 13,14) was not affected by IPC.…”
Section: Physiological Responses At Maximal Work Loadmentioning
confidence: 99%
See 3 more Smart Citations